Association between Left Ventricular Thrombus Formation and Adverse Outcomes in Acute Anterior Myocardial Infarction Patients who had Undergone Primary Percutaneous Coronary Intervention - Saadat Hussain, Hafiz Abdul Kabeer, Amir Shahzad, Mian Adnan Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the association between left ventricular thrombosis (LVT) and adverse cardio-cerebrovascular events in anterior acute ST segment elevation myocardial infarction patients who had undergone primary percutaneous coronary intervention. Study design: A retrospective study. Study place and duration: From 22nd Oct 2020 to 22nd Oct 2021 at the Cardiology department of Ch.Pervaiz Elahi Institute of Cardiology Multan. Methodology: The study included patients who were identified with anterior acute ST segment elevation myocardial infarction and received primary percutaneous intervention within the first 12 hours following onset. Patients were specifically evaluated for being treated with oral vitamin K antagonists (VKA) at discharge along with their assessment of the international normalized ratio (INR). The primary endpoint was considered as the occurrence of major cardio-cerebrovascular events, the secondary endpoint was the resolution of thrombus in LVT patients within 1 year. Results: 4(6.6%) patients were diagnosed with LVT within a month after disease onset and 56(93%) without LVT. During one year follow up, 6(10%) patients without LVT and 1(22%) patient with LVT had gone through MACCE event at least once. According to univariate analysis, LVT is related to an increase in the risk of MACCE events. The rate of heart failure differed significantly (OR = 3.42, 95% CI (1.3-4.6)). Within a year of onset, LVT was an independent predictor of MACCE (HR =2.3, 95% CI (1.11-6.40)). Moreover, in patients with INR ≥ 2 risk of MACCE was less as compared to those with INR < 2. Conclusion: LVT is an independent predictor of 1 year adverse cardio-cerebrovascular events in subjects with ant-AMI who had undergone PPCI. Within therapeutic range ≥2 treatment consists of triple therapy. It can potentially reduce the rate of MACCE events and increase the dissolution of the thrombosis.